GAAR as tax treaty override: Slovak perspective - Andrea Koroncziová; Matej Kacaljak (DANUBE: Law, Economics and Social Issues Review, 2017)
The article summarises the views on the interrelation of GAARs and tax treaties, abstracts defining criteria for the feasibility of GAAR as an anti-abuse instrument in tax treaty situations and applies these to the situation (legislation and case law) in the Slovak Republic. The aim of the article is to provide insight on the potential interrelation of GAAR rules with existing tax treaties and formulate policy advice that should be optimal given the facts at hand. It shows that GAAR in its current form would in general have limited effectiveness in tackling tax treaty abuse situations without it resulting in treaty override. This particularly applies to the Slovak Republic and likely to other states applying a monistic approach to international treaties, where the renegotiation of the treaty seems the only viable option. However, as in Slovakia the monist approach applies only to treaties ratified after July 2001, a different approach might be taken with respect to those that are still subject to a dualist approach.
Keywords: 330; GAAR; Treaty Override; Slovak Republic; Monistic Approach; Tax Treaty